Multi-proxy evidence of Late Quaternary climate and vegetational history of north-central India: Implication for the Paleolithic to Neolithic phases. (1st February 2020) - Jha, Deepak Kumar; Sanyal, Prasanta; Philippe, Anne
Abstract: The Quaternary fluvial sequences of the Belan river in north-central India preserves the signature of prehistoric human settlement from Paleolithic to Neolithic interval. The settlement history in the Belan valley has been attributed to be driven by climatic fluctuations, although quantitative climate data from the valley is lacking. For the first time, we have analysed oxygen and carbon isotopes in soil carbonates (δ 18 OSC and δ 13 CSC ) and hydrogen and carbon isotopes in n -alkane of paleosol (δDC29 and δ 13 CC29 ) from chronologically well-constrained six archaeological sites to understand the climate-cultural relationship. The chronological sequences were refined by Bayesian statistics using ChronoModel 1.5. The δDC29 and δ 18 OSC values, proxies for rainfall, indicate two phases of isotopic depletion during ∼100 to 75 ka and ∼18 to 3 ka implying intensification of monsoon. During ∼75 to 25 ka, the δDC29 and δ 18 OSC values show fluctuation in the monsoonal rainfall. Higher δDC29 and δ 18 OSC values during ∼25 to 18 ka suggest an arid environment, which corresponds to the Last Glacial Maximum (LGM). The present study suggests that climate was the driving force for fluvial incision and aggradation at a regional scale during ∼100 to 3 ka. The δ 13 CC29 and δ 13 CSC values suggest that the C4 plants dominated in a mixed C3 -C4 environment between ∼75 and 25 ka. The abundance of C4 plants sharply decreased during the early-Holocene. Comparison between climatic conditions and the temporal variation in the number of archaeological sites suggest climate-driven shifts in population density or local migration of prehistoric humans during the Middle Paleolithic to Early Neolithic phase. Highlights: Bayesian approach based chronological model for archaeological sites. Multi-proxy evidence of Late Quaternary climate and vegetation shifts. Weak monsoon and lower p CO2 favored higher abundance of C4 plants. Early-Holocene monsoon intensification augmented rice domestication. The migration and population history was coeval with climate and vegetational shift.